2022
DOI: 10.1159/000524828
|View full text |Cite
|
Sign up to set email alerts
|

Sentinel Node Biopsy by Transvaginal Natural Orifice Transluminal Endoscopic Surgery in a Patient with Early-Stage Cervical Cancer: A Case Report

Abstract: Sentinel lymph node biopsy (SLNB) has emerged as an accurate tool to identify lymph node metastases in patients with cervical cancers. This procedure is generally performed by conventional or robotic-assisted laparoscopy, but SLNB by transvaginal natural orifice transluminal endoscopic surgery (vNOTES) has been described for the surgical staging of endometrial cancer. This transvaginal approach seems to be associated with reduced surgical morbidities and could be of particular interest in managing cancer patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…We proposed a standardized 10-step approach for SLN mapping by retroperitoneal vNOTES for patients with early-stage endometrial and cervical cancer. Since Baekelandt first described this technique in 2019 [ 12 ], only a few articles have been published on this topic, including case reports, small single-center case series, and proposals for technique modifications [ 14 , 15 , 16 , 17 , 18 , 19 , 22 ]. Following the IDEAL (Idea Development Exploration Assessment Long-term follow-up) framework, we can consider that research regarding this technique is in Stage 2a (Development), and its standardized description appeared necessary before moving to Stage 2b (Exploration), allowing for a greater surgical homogeneity required to conduct larger multi-center studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We proposed a standardized 10-step approach for SLN mapping by retroperitoneal vNOTES for patients with early-stage endometrial and cervical cancer. Since Baekelandt first described this technique in 2019 [ 12 ], only a few articles have been published on this topic, including case reports, small single-center case series, and proposals for technique modifications [ 14 , 15 , 16 , 17 , 18 , 19 , 22 ]. Following the IDEAL (Idea Development Exploration Assessment Long-term follow-up) framework, we can consider that research regarding this technique is in Stage 2a (Development), and its standardized description appeared necessary before moving to Stage 2b (Exploration), allowing for a greater surgical homogeneity required to conduct larger multi-center studies.…”
Section: Discussionmentioning
confidence: 99%
“…The retroperitoneal vNOTES approach appears to be the most promising, providing easy visualization of lymphatic afferent vessels and pelvic lymph nodes (LNs), early LN assessment, and a coherent mapping methodology following the lymphatic flow from caudal to cranial [ 14 ]. Although this technique appears to be a possible revolutionary tool to stage endometrial and cervical cancer, only a few publications have reported it [ 12 , 14 , 15 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding other gynecological malignancies, only one case report has been published regarding vNOTES SLN biopsy in early-stage cervical cancer [ 35 ]. Similar benefits have been observed in sentinel node biopsies for endometrial cancer staging.…”
Section: Vnotes In Benign Gynecologic Conditionsmentioning
confidence: 99%
“…Since the first vNOTES of the adnexa was reported in 2012, [1][2][3] this approach has been widely used in various gynecologic procedures, such as salpingectomy, ovarian cyst removal, adnexectomy, hysterectomy, lymphadenectomy (sentinel, dissection), and pelvic floor repair. [3][4][5][6][7][8] Compared with laparoendoscopic single-site surgery (LESS), vNOTES has the advantages of mild postoperative pain, earlier anal exhaust time, and the absence of superficial scarring. [9][10][11][12][13] However, as a new surgical approach, perioperative complications are crucial assessment indicators in addition to confirming the feasibility and advantages of vNOTES.…”
Section: Introductionmentioning
confidence: 99%
“…The gynecologic surgical approach has advanced from open surgery to laparoscopy, natural orifice transluminal endoscopic surgery (NOTES), and transvaginal NOTES (vNOTES). Since the first vNOTES of the adnexa was reported in 2012, 1–3 this approach has been widely used in various gynecologic procedures, such as salpingectomy, ovarian cyst removal, adnexectomy, hysterectomy, lymphadenectomy (sentinel, dissection), and pelvic floor repair 3–8 . Compared with laparoendoscopic single‐site surgery (LESS), vNOTES has the advantages of mild postoperative pain, earlier anal exhaust time, and the absence of superficial scarring 9–13 …”
Section: Introductionmentioning
confidence: 99%